Edible flowers: a sustainable source of natural food ingredient - Krishnabrunda Duggirala; Gopinath Mummaleti; Fanbin Kong; Anupam Roy; Anand Mohan (Journal of Food Bioactives, 2024)
Edible flowers have gained popularity due to evolving dietary preferences and their recognized safety for human consumption, offering notable nutritional benefits. Utilized in culinary practices since ancient times, edible flowers are now acknowledged for their heightened health-promoting properties, expanding their market presence. Rich in nutraceutical elements like anthocyanins and antioxidants, edible flowers can be infused in beverages, incorporated into sweets or meals, and consumed in various forms. Market trends underscore the need for a comprehensive analysis of edible flowers, including their categories, origin, bioactive compounds, nutritional value, and applications in the food industry. This review explores the diverse characteristics of edible flowers, examines their functional ingredients, addresses preservation methods for extended shelf-life, and emphasizes the importance of considering potential toxicological effects. While many edible flowers offer safe consumption and health benefits, careful consideration is essential, as not all flowers are suitable for eating. This review aims to provide insights for a safe and enjoyable culinary experience.